Proton versus photon therapy for high-risk prostate cancer with dose escalation of dominant intraprostatic lesions: a preliminary planning study - Ong, Ashley Li Kuan; Knight, Kellie; Panettieri, Vanessa; Dimmock, Mathew; Tuan, Jeffrey Kit Loong; Tan, Hong Qi; Wright, Caroline (Frontiers in Oncology, 2023)
Background and purpose: This study aimed to investigate the feasibility of safe dose escalation to dominant intraprostatic lesions (DILs) and assess the clinical impact using dose-volume (DV) and biological metrics in photon and proton therapy. Biological parameters defined as late Grade ≥2 gastrointestinal (GI) and genitourinary (GU) derived from planned (DP) and accumulated dose (DA) were utilized. Materials and methods: Ten patients with high-risk prostate cancer with multiparametric MRI defined DILs were investigated. Each patient had two plans with focal boost to the DILs using intensity-modulated proton therapy (IMPT) and volumetric-modulated arc therapy (VMAT). Plans were optimized to obtain DIL coverage while respecting the mandatory organs-at-risk constraints. For the planning evaluation, DV metrics, tumor control probability (TCP) for the DILs and whole prostate excluding the DILs (prostate-DILs), normal tissue complication probability (NTCP) for the rectum and bladder were calculated. Wilcoxon signed-rank test was used for analyzing TCP and NTCP data. Results: IMPT achieved a higher Dmean to the DILs compared to VMAT (IMPT: 68.1 GyRBE vs VMAT: 66.6 Gy, p<0.05). Intermediate-high rectal and bladder doses were lower for IMPT (p<0.05), while the high dose region (V60 Gy) remained comparable. IMPT-TCP for prostate-DIL were higher compared to VMAT (IMPT: 86%; α/β=3, 94.3%; α/β=1.5 vs VMAT: 84.7%; α/β=3, 93.9%; α/β=1.5, p<0.05). Likewise, IMPT obtained a moderately higher DILs TCP (IMPT: 97%; α/β=3, 99.3%; α/β=1.5 vs VMAT: 95.9%; α/β=3, 98.9%; α/β=1.5, p<0.05). Rectal DA-NTCP displayed the highest GI toxicity risk at 5.6% and IMPT has a lower GI toxicity risk compared to VMAT predicted Quantec-NTCP (p<0.05). Bladder DP-NTCP projected a higher GU toxicity than DA-NTCP, with VMAT having the highest risk (p<0.05). Conclusion: Dose escalation using IMPT is able to achieve a high TCP to the DILs, with the lowest rectal and bladder DV doses at the intermediate-high dose range. The reduction in physical dose was translated into a lower NTCP (p<0.05) for the bladder, although rectal toxicity remained equivalent.